A robust nonconforming H-2-element - Nilssen, Trygve K. (2009)
Finite element methods for some elliptic fourth order singular perturbation problems are discussed. We show that if such problems are discretized by the nonconforming Morley method, in a regime close to second order elliptic equations, then the error deteriorates. In fact, a counterexample is given to show that the Morley method diverges for the reduced second order equation. As an alternative to the Morley element we propose to use a nonconforming H-2-element which is H-1-conforming. We show that the new finite element method converges in the energy norm uniformly in the perturbation parameter.